Impact of Frontline Demonstrations on Varietial Evaluation of Wheat (Triticum aestivum) Under Cold Arid Condition of Kargil (J & K) - Hussain, N.; Mehdi, M.; Fatima, N.; Hussain, M.; Dar, E. A.; Zargar, K. A.; Asmat, S.; Dar, S. R. (Indian Journal of Hill Farming, 2018)
The present study was carried out by Krishi Vigyan Kendra, Kargil, to know the difference between improved package of practices with rust resistant variety (HD 2967) under Front Line Demonstration (FLD) and farmer’s practice (FP) of Local wheat (Krokar) under cold arid condition of Kargil district. FLDs were conducted on 20 farmers’ fields each year to demonstrate the impact of improved agro-techniques with high yielding rust resistant wheat on production and economic benefits under Cold arid condition of Kargil (Ladakh) Region during Kharif seasons of two consecutive years i.e. 2015-16 and 2016-17. The technologies demonstrated in FLDs recorded additional yield over farmers practice. Under FLDs the grain yield of wheat was increased by 7.73 q/ha over FP. Adoption of rust resistant variety HD2967 with improved package of practices in wheat cultivation recorded higher B:C ratio (1.65) as compare to FP (1.35). Yield enhancement and higher net returns observed under FLDs of improved technologies with rust resistant wheat. Thus, the productivity of wheat could be increased with the adoption of rust resistant wheat variety HD 2967with recommended improved package of practices. The present study resulted to convincing the farming community for higher productivity and returns.